Estudo de aspectos químicos, biológicos e biossintéticos em Piper fuligineum Kunth(Piperaceae) - Mazzeu, Bruna Fonseca [UNESP] (2014)
The chemical profile of leaves and fruits of Piper fuligineum was analyzed by high performance liquid chromatography. The chemical composition of medium polarity related to leaves and fruits showed great similarity. The analysis also showed that the chemical composition of the fruits was more complex, mainly due to the presence of more polar substances. These analyzes allowed the selection of the leaves of P. fuligineum to continue the chemical studies. The chemical studies of the leaves of Piper fuligienum resulted in the isolation of six compunds, including two kavalactones (4- methoxy-6- [(E)-2-phenyl -vinyl] -2H-pyran-2-one and 6-(1,2-dihydroxy-2-phenyl- ethyl)-4-methoxy-2H- pyran-2-one), one chromanone (methyl-2,2-dimethyl-4-oxo-6- cromanacarboxylate) and two prenylated derivatives of benzoic acid (methyl-4-hydroxy-3-(3-methyl-2- buten-1-yl) benzoate and methyl-4-methoxy-3-(3-methyl -2-butenoyl) benzoate. The chemical structures of the isolated compounds were determined using spectrometric techniques, including 1D and 2D NMR. All compounds were described for the first time in Piper fuligineum, and the compound 4 is a new natural product. The ethanolic leaf extract and fractions obtained from P. fuligineum were evaluated for trypanocidal potential against epimastigote form of Trypanosoma cruzi Y strain, showing promising activity of the ethanol extract with IC50 of 26.67 g.mL-1 compared with the positive control benznidazole, with IC50 of 11.11 g.mL-1. The ethyl acetate extract, the chloroform fraction and substance 1 underwent antifungal drugs against fungi Candida albicans, C.krusei, C. tropicalis, C. parapsilosis and Cryptococcus neoformans yeast. The extract showed strong activity against the fungus Candida tropicalis and moderate activity against fungi C. krusei, C. parapsilosis and Cryptococcus neoformans yeast while the chloroform fraction showed strong activity against the fungus C. krusei, and moderate activity against...